The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1038/sj.bjc.6602617
|View full text |Cite
|
Sign up to set email alerts
|

An overview of menopausal oestrogen–progestin hormone therapy and breast cancer risk

Abstract: Results from the Women's Health Initiative (WHI) trial support findings from observational studies that oestrogen -progestin therapy (EPT) use is associated with an increase in breast cancer risk. We conducted a meta-analysis using EPT-specific results from the Collaborative Group on Hormonal Factors in Breast Cancer (CGHFBC) pooled analysis and studies published since that report to obtain an overview of EPT use and breast cancer risk. We also assessed risk by histologic subtype of breast cancer, by schedule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
94
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(110 citation statements)
references
References 41 publications
(88 reference statements)
13
94
0
3
Order By: Relevance
“…Our results are consistent with a promoting effect of progestagens on tumour cells, by showing an increase in risk with Cancer, 1996Cancer, , 1997Lee et al, 2005) suggesting that the increase in risk might be limited to current use of hormonal treatments. Our study had some limitations.…”
Section: Discussionsupporting
confidence: 88%
“…Our results are consistent with a promoting effect of progestagens on tumour cells, by showing an increase in risk with Cancer, 1996Cancer, , 1997Lee et al, 2005) suggesting that the increase in risk might be limited to current use of hormonal treatments. Our study had some limitations.…”
Section: Discussionsupporting
confidence: 88%
“…With respect to use of hormone replacement therapy (HRT), several studies have indicated that HRT use increases the risk of BC. The risk is even higher with longer duration of use and most specifically with the use of estrogen-progestin combination [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Moreover, case-control investigations of variable sample size and characteristics have also been performed during the last 3 decades. 5,6 The collective evidence for most of the investigated mammotropic hormones 1 -including estrone, estradiol, androstenedione, dehydroepiandrosterone sulfate (DHEAS) and testosterone-as well as prolactin, 2 insulin-like growth factor 1 (IGF-1) 7 and perhaps, on the basis of evidence regarding hormone replacement treatment, even progesterone, 8 suggests that they are positively associated with breast cancer risk. Only for adiponectin, there is evidence that it may be inversely associated with breast cancer risk.…”
mentioning
confidence: 99%